Time of the child - Williams, Niall, 1958- (Bloomsbury Publishing, 2024)
Doctor Jack Troy was born and raised in Faha, but his responsibilities for the sick and his care for the dying mean he has always been set apart from the town. His eldest daughter, Ronnie, has grown up in her father's shadow, and remains there, having missed one chance at love - and passed up another offer of marriage from an unsuitable man. But in the Advent season of 1962, as the town readies itself for Christmas, Ronnie and Doctor Troy's lives are turned upside down when a baby is left in their care. As the winter passes, father and daughter's lives, the understanding of their family, and their role in their community are changed forever. Set over the course of one December in the same village as Williams' beloved This Is Happiness, Time of the Child is a tender return to Faha for readers who know its charms, and a heartwarming welcome to new readers entering for the very first time.